Histological Effect of Androgenic Anabolic Steroide Dianabol in Heart and Some Blood Parameters of Male Albino Rats - Ahmed Obaid Hossain (Journal of Global Pharma Technology, 2018)
Anabolic androgenic steroids (AAS) standup between the drugs most broadly ill-treated with the goalmouth of improving athletic ability, appearance or muscle mass. Androgenic anabolic steroid (AAS) the most widespread types of steroids in general and particularly between young people as it works to increase the body’s metabolism, The current study was performed to examine effect of androgenic anabolic steroid dianabol in heart and some blood parameters for male Albino rat . In this research the rats were divide in to three groups, ( 4 replicates for each) . The first group control was orally received normal saline for such period . while the second group (t2) and third (t3) treated groups orally received dianabol suspension at concentrations 30 and 50 mg/kg/day for 8 weeks respectively. The results in heart tissue (both groups) show mild hemorrhage and no singes of necrosis in the tissues. The results showed that significant increase`(P<0.05) in RBC count , platelets total , Hb , p.c.v and ratio of lymphocytes in treatmssents groups compared with control , while the WBCs count show significant decrease (p<0.05) in percentages of granulocytes and monocytes, furthermore